Genome-Wide Analysis of the YABBY Transcription Factor Family in Rapeseed (Brassica napus L.) - Xia, Jichun (Genes (Basel), 2021)
The YABBY family of plant-specific transcription factors play important regulatory roles during the development of leaves and floral organs, but their functions in Brassica species are incompletely understood. Here, we identified 79 YABBY genes from Arabidopsis thaliana and five Brassica species (B. rapa, B. nigra, B. oleracea, B. juncea, and B. napus). A phylogenetic analysis of YABBY proteins separated them into five clusters (YAB1–YAB5) with representatives from all five Brassica species, suggesting a high degree of conservation and similar functions within each subfamily. We determined the gene structure, chromosomal location, and expression patterns of the 21 BnaYAB genes identified, revealing extensive duplication events and gene loss following polyploidization. Changes in exon–intron structure during evolution may have driven differentiation in expression patterns and functions, combined with purifying selection, as evidenced by K(a)/K(s) values below 1. Based on transcriptome sequencing data, we selected nine genes with high expression at the flowering stage. qRT-PCR analysis further indicated that most BnaYAB family members are tissue-specific and exhibit different expression patterns in various tissues and organs of B. napus. This preliminary study of the characteristics of the YABBY gene family in the Brassica napus genome provides theoretical support and reference for the later functional identification of the family genes.